Mediating effect of organisational support on the relationship between individual and environmental factors and acceptance of change among administrators in Malaysian public service - Samah, Safuwan (2017)
Organisations nowadays are constantly implementing changes to improve their work processes and outcomes to keep up with the changing demands. In the field of organisational change, the employees’ behaviour towards change is likely to have a substantial impact on the progress and outcome of the organisation. This study was conducted to determine whether individual factors (i.e. locus of control and attitude towards change) and environmental factors (i.e. subjective norms and social influence) will influence acceptance of change behaviour in the presence of organisational support as a mediating variable. This study adopted quantitative research paradigm using correlational research methodology. Data were collected from 400 Administrative and Diplomatic Officers (ADO) from the Management and Professional Group in the Malaysian Public Service organisation. Structural Equation Modeling (SEM) was employed to investigate the structural model of the study. Result from the direct effect analysis showed that organisational support, attitude towards change, subjective norms and social influence significantly influenced the acceptance of change behaviour. More specifically, these results suggested that organisational support plays an important role in predicting the positive behaviour during the organisational change. Other than that, attitude towards change was also found to have positive effects on the employees’ feeling of receptiveness towards any changes taking place in the organisation and embracing the changes with a positive mindset. In addition, the environmental factors (i.e. subjective norms and social influence) should not also be underestimated. Both factors offer several advantages during organisational change. Findings from the SEM also indicated that subjective norms and social influence indirectly influenced the acceptance of change behaviour through the mediating role of organisational support. Organisational support is important as it guarantees assistance for the employees provided by the organisation to deal with the challenging situations during changes. Employees with higher level of organisational support are likely to have positive attitudes and behaviours. Therefore, clear information regarding on their new task can be enhanced with the support from higher management. Besides, this study also found that people with high level of subjective norms probably experienced higher satisfaction towards their organisational support since they really appreciate the interpersonal relationship. This study is in line with the notion of Organisational Support Theory which generally believes that the employees form about how much the organisation values their contribution will help employees to develop a reciprocity norm to care about the organisation and help it achieve its goal. In addition, this study also provides new information for the Human Resource Development practitioner. This study can be used as input during change process in the context of public organisation especially in Malaysia. This study also supports the Social Cognitive Theory and Theory of Reasoned Action in emphasizing the importance of individual-related and environmental-related factors on the acceptance of change behaviour among the administrators in the public service organisation.